Microstructures and mechanical properties of additively manufactured Fe–21Mn-0.6C TWIP steel using laser powder bed fusion - Chen, Youyun (2024)
Twinning induced plasticity (TWIP) high manganese steel exhibits high ultimate tensile strength (UTS) and ductility, but its low yield strength restricts its applications. This research presents a Fe–21Mn-0.6C TWIP steel with enhanced mechanical properties additively manufactured using laser powder bed fusion (LPBF). The average grain size of the LPBF-fabricated Fe–21Mn-0.6C was 17.1 μm in the vertical direction, which was a quarter of that of a wrought one. The tensile yield strength was 657 MPa and the UTS was 1089 MPa with an elongation of 47.9% for the vertical direction. Compared to the wrought Fe–21Mn-0.6C, the yield strength increased by 110%. The high strength of LPBF-fabricated Fe–21Mn-0.6C is primarily attributed to solution, grain boundary and dislocation strengthening. Serrations were observed in the stress-strain curves at the initial stage of deformation, showing large stress drops. In the annealed sample, serrations appeared at a later stage of deformation with little stress drops. This difference in serration phenomenon is attributed to the varying dislocation density in the two samples.